2018
DOI: 10.7196/sajog.1314
|View full text |Cite
|
Sign up to set email alerts
|

An audit of the labour epidural analgesia service at a regional hospital in Gauteng Province, South Africa

Abstract: Background. Neuraxial analgesia in the form of a labour epidural has been shown to be the most effective analgesic strategy for the labouring mother. In developed countries, data are readily available as to the number of women receiving labour epidural analgesia, as well as the complication rates of labour epidurals. However, data for South Africa (SA) on labour epidural analgesia services are limited, and there were no published data for Rahima Moosa Mother and Child Hospital (RMMCH), Johannesburg, SA. Object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
3
3
1
Order By: Relevance
“…The findings from this study showed that the demand for labor epidural analgesia was very low (2.6%) which was comparable with the results from other African settings. This agrees with previous South African independent reports of level of labor epidural utilization of 1.6% and 2.2% respectively [10,11]. It is also lower than 7.5% reported by Ezeonu in Abakiliki Nigeria and 10.6% reported by Olaleye et al in Ilesha, Nigeria [5].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings from this study showed that the demand for labor epidural analgesia was very low (2.6%) which was comparable with the results from other African settings. This agrees with previous South African independent reports of level of labor epidural utilization of 1.6% and 2.2% respectively [10,11]. It is also lower than 7.5% reported by Ezeonu in Abakiliki Nigeria and 10.6% reported by Olaleye et al in Ilesha, Nigeria [5].…”
Section: Discussionsupporting
confidence: 91%
“…Our study further noted that educated women dominated the demand for epidural analgesia because they are better informed about the trending events especially as it concerns their reproductive health. This submission therefore suggests that their knowledge of epidural technique for labor pains could have contributed to the level of demand observed which corroborated the reports of other authors [10][11][12][13].Additionally, parturients who utilized labour epidurals were significantly older than 30 years of age (p=0.002), multiparous (p=0.001), and were higher income earners (p=<0.001) This was in consistent with previous Vietnam Study [1]. .Apart from the knowledge of labor epidural analgesia, a few other concerns had continued to challenge its wide use in our setting which included the effect of epidural analgesia on the outcome of labor in terms of progress of labor, mode of delivery and backache.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…[19][20] This may be a result of similar limitations in service delivery in most public maternity hospitals, but further research is needed to determine this. The epidural rates were higher in public hospitals in 2015 than those reported in a study conducted by Leonard et al [21] This is most likely a result of the initiation of a 24/7 labour epidural service in 2015 at the same GP academic hospital initially evaluated by Leonard et al [21] in 2014.…”
Section: Discussionmentioning
confidence: 77%
“…Data available from two isolated public hospital audits suggest that the epidural frequency in public hospitals is <10%, and may be as low as 2.5%. [19][20][21] The highest number of births (n=296 621) were registered in Gauteng Province (GP) in 2015, [22] and represented 27% of the registered births in SA at the time. [22] Given the high number of births in the province and the lack of information on the provision of labour epidurals, to our knowledge, we conducted the first multisite survey of labour epidural provision in the private and public sector hospitals in GP.…”
mentioning
confidence: 99%